Systemic treatments for metastatic cutaneous melanoma - Pasquali, Sandro (Cochrane Database Syst Rev, 2018)
BACKGROUND: The prognosis of people with metastatic cutaneous melanoma, a skin cancer, is generally poor. Recently, new classes of drugs (e.g. immune checkpoint inhibitors and small‐molecule targeted drugs) have significantly improved patient prognosis, which has drastically changed the landscape of melanoma therapeutic management. This is an update of a Cochrane Review published in 2000. OBJECTIVES: To assess the beneficial and harmful effects of systemic treatments for metastatic cutaneous melanoma. SEARCH METHODS: We searched the following databases up to October 2017: the Cochrane Skin Group Specialised Register, CENTRAL, MEDLINE, Embase and LILACS. We also searched five trials registers and the ASCO database in February 2017, and checked the reference lists of included studies for further references to relevant randomised controlled trials (RCTs). SELECTION CRITERIA: We considered RCTs of systemic therapies for people with unresectable lymph node metastasis and distant metastatic cutaneous melanoma compared to any other treatment. We checked the reference lists of selected articles to identify further references to relevant trials. DATA COLLECTION AND ANALYSIS: Two review authors extracted data, and a third review author independently verified extracted data. We implemented a network meta‐analysis approach to make indirect comparisons and rank treatments according to their effectiveness (as measured by the impact on survival) and harm (as measured by occurrence of high‐grade toxicity). The same two review authors independently assessed the risk of bias of eligible studies according to Cochrane standards and assessed evidence quality based on the GRADE criteria. MAIN RESULTS: We included 122 RCTs (28,561 participants). Of these, 83 RCTs, encompassing 21 different comparisons, were included in meta‐analyses. Included participants were men and women with a mean age of 57.5 years who were recruited from hospital settings. Twenty‐nine studies included people whose cancer had spread to their brains. Interventions were categorised into five groups: conventional chemotherapy (including single agent and polychemotherapy), biochemotherapy (combining chemotherapy with cytokines such as interleukin‐2 and interferon‐alpha), immune checkpoint inhibitors (such as anti‐CTLA4 and anti‐PD1 monoclonal antibodies), small‐molecule targeted drugs used for melanomas with specific gene changes (such as BRAF inhibitors and MEK inhibitors), and other agents (such as anti‐angiogenic drugs). Most interventions were compared with chemotherapy. In many cases, trials were sponsored by pharmaceutical companies producing the tested drug: this was especially true for new classes of drugs, such as immune checkpoint inhibitors and small‐molecule targeted drugs. When compared to single agent chemotherapy, the combination of multiple chemotherapeutic agents (polychemotherapy) did not translate into significantly better survival (overall survival: HR 0.99, 95% CI 0.85 to 1.16, 6 studies, 594 participants; high‐quality evidence; progression‐free survival: HR 1.07, 95% CI 0.91 to 1.25, 5 studies, 398 participants; high‐quality evidence. Those who received combined treatment are probably burdened by higher toxicity rates (RR 1.97, 95% CI 1.44 to 2.71, 3 studies, 390 participants; moderate‐quality evidence). (We defined toxicity as the occurrence of grade 3 (G3) or higher adverse events according to the World Health Organization scale.) Compared to chemotherapy, biochemotherapy (chemotherapy combined with both interferon‐alpha and interleukin‐2) improved progression‐free survival (HR 0.90, 95% CI 0.83 to 0.99, 6 studies, 964 participants; high‐quality evidence), but did not significantly improve overall survival (HR 0.94, 95% CI 0.84 to 1.06, 7 studies, 1317 participants; high‐quality evidence). Biochemotherapy had higher toxicity rates (RR 1.35, 95% CI 1.14 to 1.61, 2 studies, 631 participants; high‐quality evidence). With regard to immune checkpoint inhibitors, anti‐CTLA4 monoclonal antibodies plus chemotherapy probably increased the chance of progression‐free survival compared to chemotherapy alone (HR 0.76, 95% CI 0.63 to 0.92, 1 study, 502 participants; moderate‐quality evidence), but may not significantly improve overall survival (HR 0.81, 95% CI 0.65 to 1.01, 2 studies, 1157 participants; low‐quality evidence). Compared to chemotherapy alone, anti‐CTLA4 monoclonal antibodies is likely to be associated with higher toxicity rates (RR 1.69, 95% CI 1.19 to 2.42, 2 studies, 1142 participants; moderate‐quality evidence). Compared to chemotherapy, anti‐PD1 monoclonal antibodies (immune checkpoint inhibitors) improved overall survival (HR 0.42, 95% CI 0.37 to 0.48, 1 study, 418 participants; high‐quality evidence) and probably improved progression‐free survival (HR 0.49, 95% CI 0.39 to 0.61, 2 studies, 957 participants; moderate‐quality evidence). Anti‐PD1 monoclonal antibodies may also result in less toxicity than chemotherapy (RR 0.55, 95% CI 0.31 to 0.97, 3 studies, 1360 participants; low‐quality evidence). Anti‐PD1 monoclonal antibodies performed better than anti‐CTLA4 monoclonal antibodies in terms of overall survival (HR 0.63, 95% CI 0.60 to 0.66, 1 study, 764 participants; high‐quality evidence) and progression‐free survival (HR 0.54, 95% CI 0.50 to 0.60, 2 studies, 1465 participants; high‐quality evidence). Anti‐PD1 monoclonal antibodies may result in better toxicity outcomes than anti‐CTLA4 monoclonal antibodies (RR 0.70, 95% CI 0.54 to 0.91, 2 studies, 1465 participants; low‐quality evidence). Compared to anti‐CTLA4 monoclonal antibodies alone, the combination of anti‐CTLA4 plus anti‐PD1 monoclonal antibodies was associated with better progression‐free survival (HR 0.40, 95% CI 0.35 to 0.46, 2 studies, 738 participants; high‐quality evidence). There may be no significant difference in toxicity outcomes (RR 1.57, 95% CI 0.85 to 2.92, 2 studies, 764 participants; low‐quality evidence) (no data for overall survival were available). The class of small‐molecule targeted drugs, BRAF inhibitors (which are active exclusively against BRAF‐mutated melanoma), performed better than chemotherapy in terms of overall survival (HR 0.40, 95% CI 0.28 to 0.57, 2 studies, 925 participants; high‐quality evidence) and progression‐free survival (HR 0.27, 95% CI 0.21 to 0.34, 2 studies, 925 participants; high‐quality evidence), and there may be no significant difference in toxicity (RR 1.27, 95% CI 0.48 to 3.33, 2 studies, 408 participants; low‐quality evidence). Compared to chemotherapy, MEK inhibitors (which are active exclusively against BRAF‐mutated melanoma) may not significantly improve overall survival (HR 0.85, 95% CI 0.58 to 1.25, 3 studies, 496 participants; low‐quality evidence), but they probably lead to better progression‐free survival (HR 0.58, 95% CI 0.42 to 0.80, 3 studies, 496 participants; moderate‐quality evidence). However, MEK inhibitors probably have higher toxicity rates (RR 1.61, 95% CI 1.08 to 2.41, 1 study, 91 participants; moderate‐quality evidence). Compared to BRAF inhibitors, the combination of BRAF plus MEK inhibitors was associated with better overall survival (HR 0.70, 95% CI 0.59 to 0.82, 4 studies, 1784 participants; high‐quality evidence). BRAF plus MEK inhibitors was also probably better in terms of progression‐free survival (HR 0.56, 95% CI 0.44 to 0.71, 4 studies, 1784 participants; moderate‐quality evidence), and there appears likely to be no significant difference in toxicity (RR 1.01, 95% CI 0.85 to 1.20, 4 studies, 1774 participants; moderate‐quality evidence). Compared to chemotherapy, the combination of chemotherapy plus anti‐angiogenic drugs was probably associated with better overall survival (HR 0.60, 95% CI 0.45 to 0.81; moderate‐quality evidence) and progression‐free survival (HR 0.69, 95% CI 0.52 to 0.92; moderate‐quality evidence). There may be no difference in terms of toxicity (RR 0.68, 95% CI 0.09 to 5.32; low‐quality evidence). All results for this comparison were based on 324 participants from 2 studies. Network meta‐analysis focused on chemotherapy as the common comparator and currently approved treatments for which high‐ to moderate‐quality evidence of efficacy (as represented by treatment effect on progression‐free survival) was available (based on the above results) for: biochemotherapy (with both interferon‐alpha and interleukin‐2); anti‐CTLA4 monoclonal antibodies; anti‐PD1 monoclonal antibodies; anti‐CTLA4 plus anti‐PD1 monoclonal antibodies; BRAF inhibitors; MEK inhibitors, and BRAF plus MEK inhibitors. Analysis (which included 19 RCTs and 7632 participants) generated 21 indirect comparisons. The best evidence (moderate‐quality evidence) for progression‐free survival was found for the following indirect comparisons: • both combinations of immune checkpoint inhibitors (HR 0.30, 95% CI 0.17 to 0.51) and small‐molecule targeted drugs (HR 0.17, 95% CI 0.11 to 0.26) probably improved progression‐free survival compared to chemotherapy; • both BRAF inhibitors (HR 0.40, 95% CI 0.23 to 0.68) and combinations of small‐molecule targeted drugs (HR 0.22, 95% CI 0.12 to 0.39) were probably associated with better progression‐free survival compared to anti‐CTLA4 monoclonal antibodies; • biochemotherapy (HR 2.81, 95% CI 1.76 to 4.51) probably lead to worse progression‐free survival compared to BRAF inhibitors; • the combination of small‐molecule targeted drugs probably improved progression‐free survival (HR 0.38, 95% CI 0.21 to 0.68) compared to anti‐PD1 monoclonal antibodies; • both biochemotherapy (HR 5.05, 95% CI 3.01 to 8.45) and MEK inhibitors (HR 3.16, 95% CI 1.77 to 5.65) were probably associated with worse progression‐free survival compared to the combination of small‐molecule targeted drugs; and • biochemotherapy was probably associated with worse progression‐free survival (HR 2.81, 95% CI 1.54 to 5.11) compared to the combination of immune checkpoint inhibitors. The best evidence (moderate‐quality evidence) for toxicity was found for the following indirect comparisons: • combination of immune checkpoint inhibitors (RR 3.49, 95% CI 2.12 to 5.77) probably increased toxicity compared to chemotherapy; • combination of immune checkpoint inhibitors probably increased toxicity (RR 2.50, 95% CI 1.20 to 5.20) compared to BRAF inhibitors; • the combination of immune checkpoint inhibitors probably increased toxicity (RR 3.83, 95% CI 2.59 to 5.68) compared to anti‐PD1 monoclonal antibodies; and • biochemotherapy was probably associated with lower toxicity (RR 0.41, 95% CI 0.24 to 0.71) compared to the combination of immune checkpoint inhibitors. Network meta‐analysis‐based ranking suggested that the combination of BRAF plus MEK inhibitors is the most effective strategy in terms of progression‐free survival, whereas anti‐PD1 monoclonal antibodies are associated with the lowest toxicity. Overall, the risk of bias of the included trials can be considered as limited. When considering the 122 trials included in this review and the seven types of bias we assessed, we performed 854 evaluations only seven of which (< 1%) assigned high risk to six trials. AUTHORS' CONCLUSIONS: We found high‐quality evidence that many treatments offer better efficacy than chemotherapy, especially recently implemented treatments, such as small‐molecule targeted drugs, which are used to treat melanoma with specific gene mutations. Compared with chemotherapy, biochemotherapy (in this case, chemotherapy combined with both interferon‐alpha and interleukin‐2) and BRAF inhibitors improved progression‐free survival; BRAF inhibitors (for BRAF‐mutated melanoma) and anti‐PD1 monoclonal antibodies improved overall survival. However, there was no difference between polychemotherapy and monochemotherapy in terms of achieving progression‐free survival and overall survival. Biochemotherapy did not significantly improve overall survival and has higher toxicity rates compared with chemotherapy. There was some evidence that combined treatments worked better than single treatments: anti‐PD1 monoclonal antibodies, alone or with anti‐CTLA4, improved progression‐free survival compared with anti‐CTLA4 monoclonal antibodies alone. Anti‐PD1 monoclonal antibodies performed better than anti‐CTLA4 monoclonal antibodies in terms of overall survival, and a combination of BRAF plus MEK inhibitors was associated with better overall survival for BRAF‐mutated melanoma, compared to BRAF inhibitors alone. The combination of BRAF plus MEK inhibitors (which can only be administered to people with BRAF‐mutated melanoma) appeared to be the most effective treatment (based on results for progression‐free survival), whereas anti‐PD1 monoclonal antibodies appeared to be the least toxic, and most acceptable, treatment. Evidence quality was reduced due to imprecision, between‐study heterogeneity, and substandard reporting of trials. Future research should ensure that those diminishing influences are addressed. Clinical areas of future investigation should include the longer‐term effect of new therapeutic agents (i.e. immune checkpoint inhibitors and targeted therapies) on overall survival, as well as the combination of drugs used in melanoma treatment; research should also investigate the potential influence of biomarkers.